Revalidation of Oliera Brèthes (Lepidoptera: Cecidosidae) based on a redescription of O. argentinana and DNA analysis of Neotropical cecidosids - Moreira, Gilson R. P.; Gonçalves, Gislene L.; Eltz, Rodrigo P.; San Blas, Germán; Davis, Donald R. (Zootaxa, 2012)
Larvae of Oliera argentinana, Brèthes 1916 (Lepidoptera: Cecidosidae) were rediscovered inducing spindle-shaped gallsenclosed within swollen stems of Schinus (Anacardiaceae) in central Argentina and Rio Grande do Sul, the southernmoststate of Brazil. Male, female, immature stages, and plant galls of O. argentinana are redescribed, using optical andscanning electron microscopy. The genus Oliera Brèthes, 1916, previously a junior synonym of Cecidoses Curtis, 1835,is revalidated, by comparing morphological characteristics within the family and through an analysis of mitochondrial(COI) DNA sequences, including putative members of the four Neotropical cecidosid genera. Information on preliminary Cecidosidae phylogeny and taxonomy is also provided.